The Prognostic Value of p16 Hypermethylation in Cancer: A Meta-Analysis. - Xiang-Bin Xing; Wei-Bin Cai; Liang Luo; Long-Shan Liu; Hui-Juan Shi; Min-Hu Chen (PLoS ONE, 2013)
Background The prognostic value of p16 promoter hypermethylation in cancers has been evaluated for several years while the results remain controversial. We thus performed a systematic review and meta-analysis of studies assessing the impact of p16 methylation on overall survival (OS) and disease-free survival (DFS) to clarify this issue. Methods We searched Pubmed, Embase and ISI web of knowledge to identify studies on the prognostic impact of p16 hypermethylation in cancers. A total of 6589 patients from 45 eligible studies were included in the analysis. Pooled hazard ratios (HRs) with 95% confidence interval (95% CI) were calculated to estimate the effect using random-effects model. Results The analysis indicated that p16 hypermethylation had significant association with poor OS of non-small cell lung cancer (NSCLC) (HR 1.74, 95% CI: 1.36-2.22) and colorectal cancer (CRC) (HR 1.80; 95% CI 1.27-2.55). Moreover, the significant correlation was present between p16 hypermethylation and DFS of NSCLC (HR 2.04, 95% CI: 1.19-3.50) and head and neck cancer (HR 2.24, 95% CI: 1.35-3.73). Additionally, in the analysis of the studies following REMARK guidelines more rigorously, p16 hypermethylation had unfavorable impact on OS of NSCLC (HR 1.79, 95% CI: 1.35-2.39) and CRC (HR 1.96, 1.16-3.34), and on DFS of NSCLC (HR 2.12, 95% CI: 1.21-3.72) and head and neck cancer (HR 2.24, 95% CI: 1.35-3.73). Conclusions p16 hypermethylation might be a predictive factor of poor prognosis in some surgically treated cancers, particularly in NSCLC.